The Relationship Between Complementary Feeding with Breastmilk (MP-ASI) and the Incidence of Stunting in Under-Five Children - Ismarina; Lili Mutiara Maheka; Annisa Nurhayati Hidayat (KHD Production, 2024)
Complementary feeding is required from 6 months of age to fulfill children's nutritional needs. Inadequate complementary foods both in quantity and quality will have an impact on child growth, one of which is the incidence of stunting. This study aims to determine the relationship between complementary feeding (MP-ASI) and the incidence of stunting in under-fives in Cilowong Village, UPTD Puskesmas Taktakan Working Area in 2023. This type of research uses a quantitative approach where researchers observe subjects without intervening using the questionnaire method. The design used was cross-sectional and all types of measurements were taken at once, the sample used was mothers who had under-five children totaling 100 samples. The results of this study indicate that there is a relationship between the timing of complementary food, type of complementary food, texture of complementary food, frequency of complementary food, and portion of complementary food with the incidence of stunting (p=0.000). There is a significant relationship between the provision of complementary foods and the incidence of stunting.